Sir Thomas Browne Against Error: An Apology for Complexity (Altre Modernità, 2017)
In 1646 Sir Thomas Browne published his Pseudodoxia Epidemica, a broad, somewhat encyclopedic catalogue of errors divided into seven books. Browne intended his work as “Enquiries into Vulgar and Common Errors” to help discourage “radicated beliefs” – that is, received opinions based on popular credulity and the unchallenged authority of tradition. Far from being dogmatic and assertive, the treatise engages the modern reader for its defence of open debate and of the value of contradiction; actually, Pseudodoxia appears deeply in tune with the epistemological uncertainty of our times for its complex, relativising and even dubitative approach to all things human. Browne endorses the idea that uncritical acceptance of received notions about the world hinders the advancement of learning; at the same time, though, a rigidly straight path – a unique, simplified method to decipher reality – equally perverts knowledge and is the source of misapprehension and mystification. Building on recent studies on his style and his connection with a culturally and politically convulsed historical period, the present contribution discusses Browne’s notion of complexity and highlights exemplary passages in which he discusses the main source of error: the human tendency to simplify what is complex, thus reducing the interpretation of notions, signs and phenomena to a one-sided and necessarily inadequate undertaking.